Corrigendum: Effects of breathing re-education on endurance, strength of deep neck flexors and pulmonary function in patients with chronic neck pain: A randomised controlled trial - Sahreen Anwar; Syed A. Arsalan; Hamayun Zafar; Ashfaq Ahmed; Syed A. Gillani; Asif Hanif (AOSIS, 2023)
No abstract available.